Kepemimpinan dalam Manajemen Perubahan di Lingkungan Organisasi Bisnis - Laila Annisyah Lubis; Nuri Islami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Change leadership is an attempt to revolutionize organizational change to bring about empathetic change by integrating with all components within the organization to bring about change. Explain the environment surrounding the business organization. Corporate organizations as part of society are inseparable from the fact that all forms of activity are interconnected, influenced and impact the environment. The environment of a business organization can take the form of an internal and external environment as well as a local and international environment. A good understanding of the environment of a business organization will help a company carry out its business activities. By considering the environment of the business organization, it is possible to achieve the goals that the business organization should achieve.